Enhancing partnerships in special education : innovative collaboration, consultation, and cooperation - Banks, Tachelle; Obiakor, Festus E.; Rotatori, Anthony F. (Emerald Publishing Limited : Information Age Publishing, 2021)
"This book provides readers with a comprehensive description of procedures and practices that can enhance special education consultation. classroom learning environments and ancillary educational services. Experts in the field of special education provide detailed information on critical topics such as fostering the collaboration between regular education and the special education teachers, the role of mental health providers in special education, and the innovative use of technology in enhancing partnerships in general and special education. Unique chapters include the psychologist in the special education process, the role of the government as a partner to enhance special education services, and the vital role that principles play as school leaders to insure that special education students garner the necessary services to maximize their learning. Lastly, the important role that critical areas such as speech and language and physical education are discussed as to their value in optimizing the overall development of students with special needs"-- Provided by publisher.
Keywords: Special education teachers -- Professional relationships.; Group work in education.; Teaching teams.; Education -- Special Education -- General.; For specific learning difficulties.; Teaching of students with different educational needs.; elektronické knihy; electronic books